Community treatment orders in Western Switzerland: A retrospective epidemiological study. (November 2019) - Silva, Benedetta; Golay, Philippe; Boubaker, Karim; Bonsack, Charles; Morandi, Stéphane
Abstract: Purpose: Community treatment orders (CTOs) are legal procedures that authorise compulsory community mental health care to people affected by severe mental disorders. Nowadays, CTOs are regulated in 75 countries, with important variations in terms of legal criteria and practices. In Switzerland CTOs were introduced on the 1 st January 2013, following the amendment of the Swiss Civil Code. The aim of this study was to provide a first understanding of the use of CTOs in Western Switzerland in terms of incidence and prevalence rates, population profile, orders duration and reasons for discharge. Methods: Incidence and prevalence rates of CTOs between 2013 and 2017 were estimated. Survival analysis was used to investigate time to CTO discharge and associated factors. Logistic regression was performed to identify factors associated with CTOs' success as reason for discharge. Results: CTOs' incidence rates per 100'000 inhabitants ranged between 4.8 for 2013 and 9.6 for 2017, while their prevalence raised from 4.8 to 19.5. People placed under CTO were mainly male, in their forties, of Swiss origin, single and living independently. Primarily affected by Schizophrenia, schizotypal and delusional disorders (F20-F29), they frequently presented substance use problems, and severe danger for themselves. CTOs were mainly ordered by the guardianship authority as a form of conditional release. The estimated mean time to discharge was almost three years. Not being of Swiss origin and being prescribed to take a medication were associated with longer CTO while living in hospital, as a consequence of a long-lasting hospitalisation, and having a non-medical professional in charge of the order were associated with shorter time to discharge. Neither clinical factors nor legal criteria predicted time to discharge. Moreover, spending more days under CTO increased the likelihood of success at discharge, whereas not being of Swiss origin reduced it. Conclusions: To the best of our knowledge, no previous studies have examined the CTOs' implementation in Switzerland. CTOs prevalence increased rapidly despite the lack of evidence on positive outcomes. Our results suggested that once under CTO, it takes a long time for a patient to be released, in case of both positive and negative outcomes.